2017
DOI: 10.5005/jp-journals-10002-1220
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Thyroid Nodules with Atypia of Undetermined Significance and Follicular Lesion of Undetermined Significance in Fine Needle Aspiration Biopsy

Abstract: Aim: To correlate selected clinical and ultrasonographic (US) characteristics with the final histopathological diagnosis in patients with atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS), and whether this information can be used in planning the surgical approach. Materials and methods:It is a retrospective study including the operated cases of AUS/FLUS from 2011 to 2014 treated at one center.Results: This cohort included 87 women and 28 men. To test for indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…16 In the present study, the majority of patients were female )84%(, which is consistent with previous studies. 11,14 There were no significant correlations between age, gender, and pathology type )benign vs. malignant(, which is concordant with the results of a previous study. 17 Few studies have assessed the utility of the ACR TI-RADS classification for Bethesda categories III and IV.…”
Section: Patient Demographics and Us-based Morphological Features Of ...supporting
confidence: 90%
See 2 more Smart Citations
“…16 In the present study, the majority of patients were female )84%(, which is consistent with previous studies. 11,14 There were no significant correlations between age, gender, and pathology type )benign vs. malignant(, which is concordant with the results of a previous study. 17 Few studies have assessed the utility of the ACR TI-RADS classification for Bethesda categories III and IV.…”
Section: Patient Demographics and Us-based Morphological Features Of ...supporting
confidence: 90%
“…The present study included both Bethesda category III and IV nodules; previously published studies from Saudi Arabia only included Bethesda category III nodules. 11,12 Cytologically indeterminate thyroid nodules are known for their heterogeneity and ambiguity. In this study, the AUS/FLUS rate was 6.4% )recommended range: <7%( and the FN/SFN rate was 3.6% )recommended range: 1-25%(.…”
Section: Patient Demographics and Us-based Morphological Features Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty seven studies comprising 3932 AUS/FLUS nodules with RFNA were used to calculate the expected prevalence of cytological categories on RFNA following an initial AUS/ FLUS diagnosis (3,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37) (Table 2). Using a random-effects model, the expected redistribution of nodules among the Bethesda categories after RFNA was 4% (95% CI: 3%, 5%) as non-diagnostic (B-I); 48% (95% CI: 43%, 54%) as benign (B-II); 26% (95% CI: 20%, 32%) as AUS/FLUS (B-III); 4% (95% CI: 3%, 6%) as follicular neoplasm (B-IV); 5% (95% CI: 3%, 6%) as suspicious for malignancy (B-V); 2% (95% CI: 1%, 2%) as malignant (B-VI).…”
Section: Distribution Of Cytological Categories On Rfna Following An ...mentioning
confidence: 99%
“…No significant correlation was found between the ultrasound findings and the final diagnosis of nodules with AUS. 10 Layfield et al identified malignancy in 36 cases out of the total 127 cases of AUS that underwent surgical exploration (28.3%). 11 The malignancy risk found by Gucon et al is 15.7%.…”
Section: The Aus Category: Discussionmentioning
confidence: 99%